ELECTRON-SPIN-LATTICE AND NUCLEAR-SPIN-LATTICE RELAXATION AND THE METAL-NONMETAL TRANSITION IN LITHIUM-METHYLAMINE SOLUTIONS - Edwards, P; Buntaine, J; Sienko, M (1979)
Electron-spin-resonance studies of fluid solutions of lithium in anhydrous methylamine are reported. Electron-spin-lattice relaxation times (T1e) are reported for solution compositions ranging from 2 to 33.6 mole% metal (MPM). Values of T1e increase by an order of magnitude as the system moves through a metal-nonmetal transition located at approximately 14 MPM. In contrast previously published nuclear- (Li7) spin-lattice relaxation times (T1n) decrease by approximately two orders of magnitude in the transition from the itinerant- to localized-electron regime. An emphasis is placed on the contrasting relaxation behavior of both nuclear and electron spins in the two regimes. In the case of electron-spin relaxation, it is argued that the transition brings about fundamental changes in the nature of the electron (spin) response to external fluctuations at the Larmor frequency. Corresponding changes in the nuclear relaxation behavior in the transition region are assessed in terms of the localization of unpaired electrons at a particular nuclear site. Specifically, electron-nuclear reside times (TNMR) are evaluated as a function of lithium composition, with TNMR10-15sec at20MPM and 5×10-14sec at5 MPM. The compositional dependence of this parameter is of considerable importance both in the discussion of changes in the magnetic (nuclei and electron) properties in the transition region and in the nature of the transition. The implications of these investigations to the nature of the metal-nonmetal transition in lithium-methylamine solutions are discussed. In particular, it is established that changes in both magnetic resonance (NMR, ESR) and transport properties in the lithium-methylamine system (attributed to delocalization of the electronic wave function) occur at approximately the same lithium concentration. In contrast, corresponding studies of the sodium-ammonia system at temperatures close to the critical consolute temperature yield different values for the critical concentration when one compares the magnetic resonance and transport properties. In this regard we emphasize the important differences in intrinsic sensitivity of the two techniques in monitoring the onset of electron delocalization. We suggest that the apparent coincidence in critical concentration in the lithium-methylamine system is indirect evidence against large-scale inhomogeneities in the transition region. A description of the transition in this system is given which attempts to incorporate both the effects of electron-electron correlations and disorder. © 1979 The American Physical Society.